2016
DOI: 10.1177/1056492616675977
|View full text |Cite
|
Sign up to set email alerts
|

The Story of Captain Baby Face and the Coffee Maker: An Entrepreneurial Narrative Perspective on Corruption

Abstract: This article calls into question the frequently used negative moral labels assigned to corruption by describing gift giving as a form of narrative entrepreneurship that bridges ontologies between public service organizations. To effectively make the comparison, this article utilizes a unique methodology to explore corruption: the layered account autoethnography. The empirical setting of this story is a jointly operated military corrections facility in Iraq. It illustrates how gaps were perceived in the U.S.–Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…With no universal rules for how autoethnographic inquiry should be structured (Pelly, 2017) but with Anderson's (2006) principles in mind, my research design is best understood as structured, overlapping stages of data collection, data production, and reflexive analysis. Importantly, writing is both data production and analysis combined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With no universal rules for how autoethnographic inquiry should be structured (Pelly, 2017) but with Anderson's (2006) principles in mind, my research design is best understood as structured, overlapping stages of data collection, data production, and reflexive analysis. Importantly, writing is both data production and analysis combined.…”
Section: Methodsmentioning
confidence: 99%
“…However, as the method should serve the research question(s), I plan to interrogate my own creative writing with an additional stage of analysis to achieve what Learmonth and Humphreys (2011) call "double autoethnography" that seeks "to be both evocative, and to have analytic engagement" (p. 105) with relevant academic conversations. Notable recent examples of this approach in organization studies include R. Pelly's (2016Pelly's ( , 2017 account of his experiences in the U.S. military and Liu's (2018) compelling tale of the postfeminist rise and fall of an academic poster girl.…”
Section: Evocative or Analytic Autoethnographymentioning
confidence: 99%
“…Several autoethnographers talk of their use of memories (e.g. Jonrad, 2018; Pelly, 2017; Sobre-Denton, 2012). Some of these memories are drawn from a considerable time ago, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it has been documented that lower level staff experience stress when organizational demands are irreconcilable with their individual ethical beliefs (Hanna, 2004; Kälvemark, Höglund, Hansson, Westerholm, & Arnetz, 2004). Studies have also shown that employees resisted or raised moral objections against unsound or immoral organizational choices, power use, and policy plans (Greenbaum, Mawritz, Mater, & Priesemuth, 2013; Lawrence & Robinson, 2007; Pelly 2017; Resick, Hargis, Shao, & Dust, 2013; Sonenshein, 2009). Deviance, next, has been reported to emerge from personal disagreement with the dominant moral order in an organization (Bloom & White, 2016; Sørensen & Villadsen, 2017) or failing moral leadership (Pelly 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that employees resisted or raised moral objections against unsound or immoral organizational choices, power use, and policy plans (Greenbaum, Mawritz, Mater, & Priesemuth, 2013; Lawrence & Robinson, 2007; Pelly 2017; Resick, Hargis, Shao, & Dust, 2013; Sonenshein, 2009). Deviance, next, has been reported to emerge from personal disagreement with the dominant moral order in an organization (Bloom & White, 2016; Sørensen & Villadsen, 2017) or failing moral leadership (Pelly 2017). Thus, employee stress and deviance have been described as resulting from moral disagreements with organizational directions or decisions.…”
Section: Introductionmentioning
confidence: 99%